The construct validity of the CODA and repeated sprint ability tests in football referees - Riiser, A.; Andersen, V.; Castagna, C.; Pettersen, S. A.; Saeterbakken, A.; Froyd, C.; Ylvisaker, E.; Naess Kjosnes, T.; Fusche Moe, V. (International Journal of Sports Medicine, 2018)
As of 2017, the international football federation introduced the change of direction ability test (CODA) and the 5×30 m sprint test for assistant referees (ARs) and continued the 6×40 m sprint test for field referees (FRs) as mandatory tests. The aim of this study was to evaluate the association between performance in these tests and running performance during matches at the top level in Norway. The study included 9 FRs refereeing 21 matches and 19 ARs observed 53 times by a local positioning system at three stadiums during the 2016 season. Running performance during matches was assessed by high-intensity running (HIR) distance, HIR counts, acceleration distance, and acceleration counts. For the ARs, there was no association between the CODA test with high-intensity running or acceleration (P>0.05). However, the 5×30 m sprint test was associated with HIR count during the entire match (E -12.9, 95% CI -25.4 to -0.4) and the 5-min period with the highest HIR count (E -2.02, 95% CI -3.55 to -0.49). For the FRs, the 6×40 m fitness test was not associated with running performance during matches (P>0.05). In conclusion, performance in these tests had weak or no associations with accelerations or HIR in top Norwegian referees during match play.